Activity Involvement and Spiritual Health in Children with ADHD and Learning Disabilities. (2nd January 2019) - Ng, Kwok; Pickett, William; Michaelson, Valerie; Freeman, John
ABSTRACT: Attention-deficit/hyperactivity disorder (ADHD) and learning disabilities (LDs) represent two of the most prevalent disabilities experienced by adolescents. Despite the benefits of spiritual health in relation to happiness and overall well-being, there has been limited examination of spiritual health among adolescents with disabilities. Sports and other activities can act as protective factors that mediate the relationship between low spiritual health and negative outcomes. Therefore, the purpose of this study was threefold: to explore the differences in spiritual health (a) among adolescents with ADHD, LDs, or without disabilities; (b) by activity type; and (c) after taking into account the interaction between disabilities and activities. Adolescents included in the 2014 (Canadian cycle 7) Health Behaviour in School-aged Children study ( n = 17, 407, M age = 14.08 years, SD = 1.46 years) reported their disability status and involvement in organized activities and completed a shortened version of Fisher's Spiritual Well-being scale. Overall spiritual health (analysis of covariance) and its dimensions (multivariate analysis of covariance) were compared by disabilities and activities with gender, age, and family affluence as covariates. Lower levels of engagement in both sports and nonsport activities were associated with diagnoses of ADHD (38.4%) and LDs (50.5%) compared with peers without disabilities (53.8%). Involvement in either sports or nonsport activities was associated with positive spiritual health outcomes ( F = 228.7, p < .001), with the highest levels of spiritual health reported by children involved in both types of activities ( F = 7.8, p < .001). The protective effect of activity involvement was stronger for children with ADHD or LDs than for children without disabilities. Diversity of activities including both sports and nonsport activities among adolescents with ADHD or LDs mitigates overall spiritual health when compared with peers without disabilities.